Math, asked by simra4825, 4 months ago

 \huge\color{pink}\mathfrak{Answer}

\sf{Prove\:That\: \frac{1 + secA}{secA}  =  \frac{ {sin}^{2}A }{1 - cosA}}


PLZ ANSWER ASAP ​

Answers

Answered by brainlyofficial11
2

\sf{To\:Prove}  \\ \bold {\: \frac{1 + secA}{secA} = \frac{ {sin}^{2}A }{1 - cosA}}

_________________________

 \bold{LHS =\frac{1 + secA}{secA} } \\

and

 \bold{RHS =\frac{ {sin}^{2}A }{1 - cosA} } \\

__________________________

first we solve LHS

\bold{LHS =\frac{1 + secA}{secA} } \\  \\ \bold{  \implies \: LHS =  \frac{1}{sec A} +   \cancel\frac{sec A}{sec A}  } \\  \\   \bold{\implies \: LHS =  \frac{1}{sec A} + 1} \:  \:  \:  \:  \:  \:  \:  \:  \:  \:

and we know that,

 \boxed{ \bold{ \frac{1}{sec A}  = cos A }}

 \bold{ \implies LHS = \: cos A + 1  } \:  \:  \:  \:  \:  \:  \:  \:  \:  \:

___________________________________

now, we solve RHS

 \bold{RHS = \frac{ {sin}^{2}A }{1 - cosA} } \\

and we know that,

 \boxed{ \bold{ {sin}^{2}A = 1 -  {cos}^{2}   A}}

and

 \bold{1 -  {cos}^{2} A = (1 - cosA)(1 + cosA)}

 \bold{ \implies RHS =  \frac{ \cancel{(1 - cosA)}(1 + cosA)}  { \cancel{1 - cosA} }} \\  \\   \bold{\implies \: RHS = 1 + cosA} \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:  \:

so, LHS = RHS

hence, proved

Answered by AbhinavRocks10
1

\color{red}\begin{gathered}\sf{To\:Prove} \\ \bold {\: \frac{1 + secA}{secA} = \frac{ {sin}^{2}A }{1 - cosA}} \end{gathered}

_________________________

\color{blue}\begin{gathered} \bold{LHS =\frac{1 + secA}{secA} } \\ \end{gathered}

\begin{gathered} \bold{RHS =\frac{ {sin}^{2}A }{1 - cosA} } \\ \end{gathered}

__________________________

first we solve LHS

\begin{gathered}\bold{LHS =\frac{1 + secA}{secA} } \\ \\ \bold{ \implies \: LHS = \frac{1}{sec A} + \cancel\frac{sec A}{sec A} } \\ \\ \bold{\implies \: LHS = \frac{1}{sec A} + 1} \: \: \: \: \: \: \: \: \: \: \end{gathered}

and we know that,

\boxed{ \bold{ \frac{1}{sec A} = cos A }}

\color{red}\bold{\implies LHS=\:cos A+1}\:⟹LHS=cosA+1

___________________________________

now, we solve RHS

\begin{gathered} \bold{RHS = \frac{{sin}^{2}A }{1 - cosA} } \\ \end{gathered}

and we know that,

\color{red}\boxed{\bold{ {sin}^{2}A = 1 - {cos}^{2} A}}

\color{aqua}\bold{1 -{cos}^{2} A = (1 - cosA)(1 + cosA)}\begin{gathered} \bold{ \implies RHS = \frac{ \cancel{(1 - cosA)}(1 + cosA)} { \cancel{1 -cosA} }} \\ \\ \bold{\implies \: RHS = 1 + cosA} \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \: \end{gathered}

(1−cosA)

⟹RHS=1+cosA

so, LHS = RHS

hence, proved

Similar questions